Effects of Electron Beam Lithography Process Parameters on the Structure of Nanoscale Devices Across Three Substrate Materials - Zhongyang Liu; Yue Chen; Xuanyu Li; Luwei Wang; Junle Qu (Photonics)
Electron beam lithography (EBL) is a pivotal technology in the fabrication of nanoscale devices, renowned for its high precision and resolution capabilities. This paper explores the effect of EBL process parameters on various substrate materials, including silicon dioxide, silicon-on-insulator (SOI), and silicon nitride. We specifically investigate the impact of the charging effect and reveal the narrow exposure dose windows necessary to achieve optimal pattern fidelity. Based on the measurement results of linewidth, the relationship between exposure dose and the width of the structure pattern after development was analyzed. The optimum exposure dose window for each substrate is identified. Furthermore, through simulations of the charge effect, we demonstrate strategies for mitigating this effect on different substrates, even in complex structural configurations. Our findings contribute to enhancing the capabilities of EBL in semiconductor and insulator manufacturing and research.